Hyperscanning EEG and Classification Based on Riemannian Geometry for Festive and Violent Mental State Discrimination - Simar, Cédric; Cebolla, Ana-Maria; Chartier, Gaëlle; Petieau, Mathieu; Bontempi, Gianluca; Berthoz, Alain; Cheron, Guy (Frontiers in Neuroscience, 2020)
Interactions between two brains constitute the essence of social communication. Daily movements are commonly executed during social interactions and are determined by different mental states which may express different positive or negative behavioral intent. In this context, the effective recognition of festive or violent intent before the action execution remains crucial for survival. Here, we hypothesize that the EEG signals contain the distinctive features characterizing movement intent already expressed before movement execution and that such distinctive information can be identified by state-of-the-art classification algorithms based on Riemannian geometry. We demonstrated for the first time that a classifier based on covariance matrices and Riemannian geometry can effectively discriminate between neutral, festive and violent mental states only on the basis of non-invasive EEG signals in both the actor and observer participants. These results pave the way for new electrophysiological discrimination of mental states based on non-invasive EEG recordings and cutting-edge machine learning techniques.